E-Commerce Management System - Logistics 1 (Project Management, Asset Management, Warehousing, Procurement): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The primary goal of this system is to have a dependable and smooth project and productmonitoring and evaluation process in e-commerce logistics. 1. In order for users to know theproject progress, monitor, and order incoming and outgoing products, the system mustmanage project management, asset management, warehousing, and procurement. Thissystem is designed to provide status information and identify work on the company's behalf.The main goal is to develop a system that will assist Logistics 1 employees in completing theirwork more quickly by utilizing an automated system rather than a manual procedure.The development team established project management, asset management, warehousing,and procurement departments. This system will assist the logistics staff in monitoring andevaluating every project and product that comes into the company. A programmer created asystem that will assist both staff in managing work monitoring and evaluation. The system willgreatly benefit e-commerce and logistics by reducing their workload and the manual labor oflogistics personnel.The developed system is a huge help to the logistics staff. We need to collaborate with everycompany and worker, especially now that we're facing an economic standard, so thedevelopment team creates a system that will help the eCommerce and logistics staff monitorand evaluate all the projects and products from every department.
Keywords: Information Systems